The Complete Guide for People With Parkinson's Disease and Their Loved Ones - Marie, Lianna, 1974- (Book collections on Project MUSE., 2020)
"A diagnosis of Parkinson's disease is as disorienting as it is devastating. The Complete Guide for People With Parkinson's Disease and Their Loved Ones helps make sense of what comes next and what can be done, not just for those suffering from the disease but for their family and friends as well. A trained nurse and primary caregiver for her mother, who was diagnosed with Parkinson's disease in 1991, Lianna Marie draws upon over twenty years of education, research, and direct experience. Written in straightforward and easily accessible language, this essential guide aims to help patients better understand their role in their treatment so that they may continue to lead happy and hopeful lives. Topics covered include nutrition and exercise, alternative and complementary therapies, medication and treatment, and what caregivers can do to help. Written by an international expert on Parkinson's who has confronted the disease firsthand, The Complete Guide serves as the go-to book for comprehensive, easy-to-understand information for all Parkinson's patients and their loved ones"--